The relationship between childhood emotional neglect experience and depressive symptoms and prefrontal resting functional connections in college students: The mediating role of reappraisal strategy - Xu, Bin; Wei, Shilin; Yin, Xiaojuan; Jin, Xiaokang; Yan, Shizhen; Jia, Lina (Frontiers in Behavioral Neuroscience, 2023)
This study recruited two groups of college students with primary childhood emotional neglect (CEN) (neglect group) and without childhood trauma (control group) to explore the relationships between CEN, adulthood emotion regulation, depressive symptoms and prefrontal resting functional connections. The methods used in this study included Childhood Trauma Questionnaire (CTQ), Emotion Regulation Questionnaire (ERQ), Beck Depression Inventory-II (BDI-II) and resting-state functional magnetic resonance imaging (rs-fMRI). The results showed that, compared with the control group, the neglect group utilized the reappraisal strategy less frequently and displayed more depressive symptoms. The prefrontal functional connections with other brain regions in the neglect group were more robust than those in the control group using less stringent multiple correction standards. Across two groups, the functional connection strength between the right orbitofrontal gyrus and the right middle frontal gyrus significantly negatively correlated with the ERQ reappraisal score and positively correlated with the BDI-II total score; the ERQ reappraisal score wholly mediated the relationship between the function connection strength and the BDI-II total score. It suggests that primary CEN may correlate closely with more depressive symptoms in adulthood. Furthermore, the more robust spontaneous activity of the prefrontal lobe may also be closely associated with more depressive symptoms by utilizing a reappraisal strategy less frequently.